'Living Rights', rights claims, performative citizenship and young people – the right to vote in the Scottish independence referendum. Issue 5 (4th July 2018) - Sanghera, Gurchathen; Botterill, Katherine; Hopkins, Peter; Arshad, Rowena
ABSTRACT: This paper examines the rights claims-making that young people engaged in during the 2014 Scottish independence referendum when the right to vote was extended to 16- and 17-year-olds for the first time in the UK. Understanding citizenship and rights claims-making as performative, we draw on the novel idea of 'living rights' to explore how young people 'shape what these rights are – and become – in the social world'. They are co-existent and situated within the everyday lives of young people, and transcend the traditional idea that rights are merely those that are enshrined in domestic and/or international law. We explore the complex and contested nature of rights claims that were made by young people as 'active citizens' in the lead up to the referendum to illustrate how the rights claims-making by young people is bound up with the performativity of citizenship that entails identity construction, political subjectivity (that challenges adult-centric approaches) and social justice.